FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN SAK EMKM PADA PENYUSUNAN LAPORAN KEUANGAN UMKM KABUPATEN JEMBER - Nata, Istiknaful Aulia; Astuti, Diana Dwi; Ningsih, Wiwik Fitria (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
The rapid advancement of time and technology has significantly impacted the existence of Micro, Small, and Medium Enterprises (MSMEs). However, MSMEs still face certain limitations, such as the tendency to mix personal and business finances. This study aims to evaluate the influence of implementing the SAK EMKM (Financial Accounting Standards for MSMEs) in the preparation of MSME financial statements, both partially and simultaneously. The research population consisted of 79,460 MSMEs, and a random sampling technique was used to select 100 respondents. A quantitative approach was employed in this study. The findings indicate that business scale and financial literacy do not have a significant partial effect on the implementation of SAK EMKM. On the other hand, accounting and financial statement understanding, human resource quality, and MSME actors' readiness show a partial influence on the application of SAK EMKM in preparing financial reports. However, when considered simultaneously, business scale, accounting and financial statement understanding, financial literacy, human resource quality, and the readiness of MSME actors all influence the implementation of SAK EMKM in the preparation of MSME financial statements.